1980
DOI: 10.1073/pnas.77.11.6516
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the regulatory component of adenylate cyclase.

Abstract: The regulatory component (G/F) of adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] from rabbit liver plasma membranes has been purified essentially to homogeneity. The purification was accomplished by three chromatographic procedures in sodium cholate-containing solutions, followed by three steps in Lubrol-containing solutions. The specific activity of G/F was enriched 2000-fold from extracts of membranes to 3-4 mumol x min-1 x mg-1 (reconstituted adenylate cyclase activity). Purified G/F re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
171
0
2

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(182 citation statements)
references
References 21 publications
9
171
0
2
Order By: Relevance
“…The Mr-values of 42 000 and 50 000, estimated for the 2 major pancreatic bands, was comparable to that of ADP-ribosylated polypeptides from other G/F oligoproteins [7,12,14] and, further, the mobilities of the 42 kM r pancreatic component ( fig.2A(2)) and of the single 42 kM r component from human erythrocyte ghosts [8,9], labelled for comparison ( fig.2A(4)) were the same.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…The Mr-values of 42 000 and 50 000, estimated for the 2 major pancreatic bands, was comparable to that of ADP-ribosylated polypeptides from other G/F oligoproteins [7,12,14] and, further, the mobilities of the 42 kM r pancreatic component ( fig.2A(2)) and of the single 42 kM r component from human erythrocyte ghosts [8,9], labelled for comparison ( fig.2A(4)) were the same.…”
mentioning
confidence: 59%
“…The same conclusion has been attained for polypeptides 45 kM r and 52-53 kM r in membranes from $49 lymphoma and HTCA cells [7], and polypeptides 42 kM r and 47 kM r from fibroblasts [23]. Similarly, polypeptides 45 kM r and 55 kM r are the only one to be ADP-ribosylated by cholera toxin in G/F from rat liver membranes, a 130 kM r oligoprotein made of 3 polypeptides: 30 kMr, 45 kM r and 55 kM r [14]. In contrast, there is only one ADP-ribosylated polypeptide in pigeon [5,6] and human [8,9] erythrocyte ghosts and in thymus [12] …”
Section: Discussionmentioning
confidence: 99%
“…its decay to opsin. Fluorides in the millimolar range confer upon the GDP-bound protein structural and functional properties of the GTP-bound one [4,8]. The requirement of a trace amount of aluminum was recently demonstrated for fluoride activation of hormonal systems and it was suggested that AlF: was indeed the active species [9].…”
Section: Abbreviationsmentioning
confidence: 99%
“…IAP catalyses ADP ribosylation of a cysteine residue in the asubunit of inhibitory GTP-binding (Gi) protein, and thereby blocks interactions between Gi protein and receptors (Katada and Ui, 1982;Murayama and Ui, 1983). On the other hand, CTX activates stimulatory GTP-binding (Gs) protein by ADP-ribosylating an arginine residue of the a-subunit in Gs protein (Northup et al, 1980;Hepler and Gilman, 1992). The finding that the activity of SAGP was diminished by IAP suggested the involvement of Gi protein in the expression of SAGP activity.…”
Section: Discussionmentioning
confidence: 99%